THE DEVELOPMENT OF HIGHER EDUCATION IN THE URALS: THE SEARCH OF AUTHORITIES AND CIVIL SOCIETY - Liudmila A. Dashkevich (Russian State Vocational Pedagogical University, 2015)
The purpose of this article is to identify the role of civil society in the establishment of the higher educational institutions in the Urals, and to determine the importance and activeness of the Ural intelligentsia in the process of transformation of regional education. Methods. The study is based on the methodological approaches inherent in the modernization paradigm. The methods used in the analysis and systematization of the factual material are historical-comparative, historical-genetic, and historical-systematic methods. Results. It is revealed that in the pre-revolutionary period the local authorities were active actors of modernization of regional education. Using projects, prepared with the help of intelligentsia forces, Zemstvo (Russian local assembly) and municipal councils of towns in the Urals were able to defend their interests at the highest level. The decision to open the first higher educational institutions in Yekaterinburg and Perm were carried in 1914 and 1916. Scientific novelty. It's the first time that the projects of Ural intelligentsia, which initiated the development of higher education in the Ural region, are summarized and analyzed. Practical significance. The results of the study and the facts put into scientific use can be applied in the preparation of general and specialized courses on the history of pedagogy.